Gene-based Diagnostics: Ready for Prime Time? - ADAMS, KATHERINE T. (BioCommunications LLC, 2005)
The rush is on to develop gene-based diagnostic tests that will detect diseases earlier and predict response to drugs and treatment. But the road to widespread use by physicians may be a long one.